Engaging Fathers in Effective Parenting for Preschool Children Using Shared Book Reading: A Randomized Controlled Trial. Issue 1 (2nd January 2018) - Chacko, Anil; Fabiano, Gregory A.; Doctoroff, Greta L.; Fortson, Beverly
Abstract : Engaging fathers and improving their parenting and, in turn, outcomes for their children in preventive/promotion-focused parenting interventions has been a notable, but understudied, challenge in the field. This study evaluated the effects of a novel intervention, Fathers Supporting Success in Preschoolers: A Community Parent Education Program, which focuses on integrating behavioral parent training with shared book reading (i.e., Dialogic Reading) using key conceptual models (i.e., common elements, deployment model, task shifting) to engage and improve father (i.e., male guardians) and child outcomes. One hundred twenty-six low-income, Spanish-speaking fathers and their children were recruited across three Head Start centers in urban communities and were randomized to the intervention or to a waitlist control condition. Outcomes were obtained before and immediately postintervention and included observed and father-reported parenting and child behaviors, standardized assessments of language, and father self-reported parental stress and depressive symptoms. Attendance data were also collected as a proxy measure of engagement to the intervention. Parenting behaviors (observed and father-reported), child behaviors (father-reported), and language development of the children in the intervention group improved significantly relative to those in the waitlist control condition. Effect sizes (ESs) were in the small to large range across outcomes. Fathers can be engaged in parenting interventions, resulting in improved parent and child outcomes. Greater attention must be given to methods for maximizing parenting within a family and toward developing effective, engaging, and sustainable intervention models for fathers.